Pengaruh Pupuk Bokashi Kanddang Ayam Terhadap Pertumbuhan Dan Produksi Bawang Merah (Allium Ascalonicum) - Muhamad Chairul Basrun Umanailo; La Jati Buton; Adyla Mita Lestari (Agrotekma: Jurnal Agroteknologi dan Ilmu Pertanian, 2022)
The effort taken to increase shallot production both in quality and quantity is to use fertilizer. One type of organic fertilizer that will be used is bokashi chicken manure. Bokashi is a fermentation of organic matter by inoculation of EM4 which is a mixed culture of beneficial microorganisms for plant growth such as Lactobacillus sp, photosynthetic bacteria, actinomycetes and yeast. The purpose of this study was to determine the effect of cutting tubers and applying various doses of chicken manure bokashi on the growth and production of shallots. The method used was a randomized block design in the form of a two-factor factorial where the first factor was the cutting of the seed tubers (p) which consisted of without cutting the ends of the tubers (p1) and cutting the ends of the tubers (p2). The second factor was the treatment of several doses of chicken manure bokashi (b) which consisted of several levels, namely 2 kg of chicken manure bokashi/plot (b1), 4 kg of chicken manure bokashi/plot (b2) and 6 kg of chicken manure bokashi/plot. tile (b3). There was a significant interaction between cutting tubers and the dose of bokashi chicken manure 4 kg plot-1 which affected the growth of shallot plants